2016
DOI: 10.1080/10245332.2015.1107275
|View full text |Cite
|
Sign up to set email alerts
|

rs11886868 and rs4671393 of BCL11A associated with HbF level variation and modulate clinical events among sickle cell anemia patients

Abstract: Our findings showed that the majority of patients carried genotype CT of rs11886868 and genotypes AG and GG of rs4671393 present HbF level < 15%. RR = 0.08, RR = 0.176, and RR = 0.189, respectively. The results showed a significant association between the alleles T of rs11886868 and G of rs4671393 and %HbF < 15% with P = 0.016; RR = 0.39 and P = 8.9 × 10(-3): RR = 0.567, respectively. Interestingly, the C allele of the rs11886868 and the A allele of the rs46713939 were associated with an ameliorated phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…In contrast, a higher proportion of an A allele of the rs4671393 (G-A) polymorphism of the BCL11A gene was detected among 122 Thai NTDT patients i.e., 28.7% in heterozygote form and 2.5% in the homozygote. This rs4671393 (G-A) polymorphism is associated with Hb F variation and clinical events in sickle anemia 27. As compared to other genes, more prevalence of the G allele of rs4895441 (A-G), the C allele of rs9399137 (T-C) and T allele of rs2297339 (C-T) of the HBS1L-MYB intergenic region were observed among our Thai NTDT patients.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, a higher proportion of an A allele of the rs4671393 (G-A) polymorphism of the BCL11A gene was detected among 122 Thai NTDT patients i.e., 28.7% in heterozygote form and 2.5% in the homozygote. This rs4671393 (G-A) polymorphism is associated with Hb F variation and clinical events in sickle anemia 27. As compared to other genes, more prevalence of the G allele of rs4895441 (A-G), the C allele of rs9399137 (T-C) and T allele of rs2297339 (C-T) of the HBS1L-MYB intergenic region were observed among our Thai NTDT patients.…”
Section: Discussionmentioning
confidence: 69%
“…Copy number variation analysis of the α‐globin and β‐globin gene clusters was performed by multiplex ligation‐dependent probe amplification (MRC Holland, Amsterdam, The Netherlands). We genotyped three quantitative trait loci (QTL) associated with HbF levels in peripheral blood: the Xmn I polymorphism in the haemoglobin subunit gamma 2 ( HBG2 ) promoter (rs7482144); the erythroid‐specific enhancer of BAF chromatin remodeling complex subunit 11A ( BCL11A ; rs11886868, rs1427407, rs4671393); and the HBS1L‐MYB intergenic region (rs28384513, rs9399137) 19–21 …”
Section: Methodsmentioning
confidence: 99%
“…We genotyped three quantitative trait loci (QTL) associated with HbF levels in peripheral blood: the XmnI polymorphism in the haemoglobin subunit gamma 2 (HBG2) promoter (rs7482144); the erythroidspecific enhancer of BAF chromatin remodeling complex subunit 11A (BCL11A; rs11886868, rs1427407, rs4671393); and the HBS1L-MYB intergenic region (rs28384513, rs9399137). [19][20][21]…”
Section: Genetic Testingmentioning
confidence: 99%
“…2p15-p16.1 chromosome microdeletion may lead to haploinsufficiency of BCL11A [27,28]. Some groups reported that BCL11A single-nucleotide polymorphisms (SNPs), especially rs11886868 and rs1427407, can reduce the expression of BCL11A [29,30]. Similarly, disrupt the enhancer of BCL11A gene can reduce its expression [31,32].…”
Section: Expression and Regulation Of Bcl11amentioning
confidence: 99%